2016
DOI: 10.1016/j.jjcc.2015.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic peptides for perioperative management of cardiac surgery

Abstract: Atrial natriuretic peptide (carperitide) is used to treat heart failure in Japan, while brain natriuretic peptide (nesiritide) is employed in Europe/USA. Patients undergoing cardiac surgery have a complex underlying pathologic state that features increased levels of neurohumoral factors due to activation of the renin-angiotensin-aldosterone system and/or increased sympathetic activity. We considered that perioperative administration of carperitide could be beneficial for cardiac surgery patients, and we have c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…As for long-term outcome, a previous large randomized study showed that tolvaptan had no effects on long-term mortality or heart failure-related morbidity [16]. On the other hand, carperitide was found to have a strong influence on long-term outcome because of its suppression of the renin-angiotensin-aldosterone system [13]. Although tolvaptan has been shown to have no effect on the renin-angiotensin-aldosterone system [19,21,22], its administration in heart failure patients is considered to improve short-and mid-term patient outcomes.…”
Section: Advent Of Tolvaptan and Its Effect In Patients With Congestive Heart Failurementioning
confidence: 99%
See 3 more Smart Citations
“…As for long-term outcome, a previous large randomized study showed that tolvaptan had no effects on long-term mortality or heart failure-related morbidity [16]. On the other hand, carperitide was found to have a strong influence on long-term outcome because of its suppression of the renin-angiotensin-aldosterone system [13]. Although tolvaptan has been shown to have no effect on the renin-angiotensin-aldosterone system [19,21,22], its administration in heart failure patients is considered to improve short-and mid-term patient outcomes.…”
Section: Advent Of Tolvaptan and Its Effect In Patients With Congestive Heart Failurementioning
confidence: 99%
“…Furthermore, perioperative administration of low-dose carperitide or nesiritide is considered to be beneficial following cardiac surgery. Cardiac surgery patients have been reported to achieve good long-term results with either drug, suggesting that low-dose natriuretic peptide therapy can be an important aspect of perioperative management due to possible cardioprotective and renoprotective effects [13].…”
Section: Postoperative Management After Open Heart Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…The process of NT-proBNP secretion by cardiomyocytes occurs in response to an increase in their voltage in the course of increased pre- and/or after-load. An increase in the concentration of BNP and the prohormone NT-proBNP in the blood is demonstrated, among other things, by the activation of the compensation mechanism, which already occurs in the period preceding the appearance of symptoms of heart failure [ 11 , 12 , 13 , 14 ]. The predictive ability of NT-proBNP has been reported in numerous publications on various cardiovascular disorders, including aortic stenosis, heart failure, coronary artery disease, myocardial infarction, congenital heart disease, and postoperative hemodynamic instability [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%